2013
DOI: 10.1002/hed.23426
|View full text |Cite
|
Sign up to set email alerts
|

Toxicities and costs of placing prophylactic and reactive percutaneous gastrostomy tubes in patients with locally advanced head and neck cancers treated with chemoradiotherapy

Abstract: PEG tubes placed prophylactically were associated with lower rates of strictures, aspirations, hospitalizations, and costs compared to those placed reactively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 23 publications
(56 reference statements)
4
49
0
1
Order By: Relevance
“…Most of them are given nutritional therapy only when they already have difficulty in eating such as swallowing disorders. [33][34][35][36][37] Studies have shown that prophylactic PEG can improve quality of life 38 and reduce the risk of aspiration, hospitalization, medical costs, 39 weight loss, length of stay, 40 and radiotherapy interruption rate. 15 Study has shown that early percutaneous endoscopic gastrostomy (PEG) placement can increase the completeness rate of concurrent chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Most of them are given nutritional therapy only when they already have difficulty in eating such as swallowing disorders. [33][34][35][36][37] Studies have shown that prophylactic PEG can improve quality of life 38 and reduce the risk of aspiration, hospitalization, medical costs, 39 weight loss, length of stay, 40 and radiotherapy interruption rate. 15 Study has shown that early percutaneous endoscopic gastrostomy (PEG) placement can increase the completeness rate of concurrent chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Reactive gastrostomy tube placement (i.e., only when significant weight loss and/or nutritional compromise becomes manifest during the course of treatment) versus prophylactic placement (i.e., placement prior to treatment initiation) remains controversial. 98100 Therefore, the optimal timing for initiating enteral feeding support and the route of delivery remain unclear for older patients with LA-HNSCC undergoing CRT who are more susceptible to nutritional and swallowing issues. Due to these intertwined challenges in supportive care facing these patients, prospective studies evaluating the relationships among age, swallowing, nutrition, and sarcopenia and longer-term functional outcomes among younger vs. older patients with LA-HNSCC are greatly needed.…”
Section: Methodsmentioning
confidence: 99%
“…This study could not have been conducted had we had an institutional policy requiring universal prophylactic feeding tube placement. Prophylactic feeding tube placement has been recommended at some institutions to diminish the risk of hospitalization for mucositis‐induced dehydration and/or aspiration, to support nutrition, and improve quality of life during treatment . Prophylactic placement may, however, be associated with prolonged feeding tube dependence and possibly worse long‐term swallowing outcomes .…”
Section: Discussionmentioning
confidence: 99%